Sexuality and the Dimensions of Power - Brickell, Chris (Sexuality & Culture : An Interdisciplinary Quarterly, 2009)
Power, many scholars agree, is intrinsic to the relationships between sexuality, individual experience and social dynamics. Beyond this basic agreement, though, writers and researchers have adopted different foci. This article critically reviews several approaches to the power-sex relationship, and suggests that four readily discernable but interlaced dimensions of power operate upon the sexual: definitional, regulatory, productive and unequal. As a number of examples from the literature show, these ideal typical forms twist and interweave in both theory and practice. I suggest that to be mindful of all four facets of power and their interrelationships is to account for multiplicity, and to avoid the reductive characterizations that have sometimes characterized academic writings on power and sexuality. In this way, both theory and research in the area of human sexuality can be more thoroughly conceptualized.
Keywords: approches et analyses; cours; discipline; hétérosexisme; premier cycle; queer; rapports de pouvoir; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques